Synthesis and Avidin Binding of Ruthenium Complexes Functionalized with a Light‐Cleavable Free Biotin Moiety. Issue 37 (1st October 2018) - Siewert, Bianka; Langerman, Michiel; Pannwitz, Andrea; Bonnet, Sylvestre
Abstract: Invited for the cover of this issue is the group of Sylvestre Bonnet from Leiden University, The Netherlands. The cover image shows the attachment of a free biotin group to a Ru compound by a light‐sensitive coordination bond. Abstract : Triggering the reactivity of a molecule with a light beam from outside the flask without introducing any other chemical is still fascinating to me after more than ten years of photochemistry research… Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by S. Bonnet et al.